2022
DOI: 10.1021/acsaem.2c02235
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Long-Plate SnWO4 Photoanode Exposed Active Facets for Enhanced Solar Water Splitting

Abstract: α-SnWO4 is a potential catalyst for photoelectrochemical (PEC) water splitting with its narrow band gap and suitable band position, while its PEC performance is restricted by poor carrier transport ability. Herein, morphology control together with facet engineering as a strategy is used to optimize the carrier transport of the SnWO4 film photoanode. In this paper, a two-dimensional (2D) long-plate structure for the SnWO4 film was obtained from a rod-like WO3 film due to the inherited behavior of the morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Fig. 2f and g display the SEM images of the precursor WO 3 and the resulting α-SnWO 4 nanorod arrays obtained by Qiu et al , 56 respectively. These images reveal that the conversion process did not significantly alter the morphology of the nanorods, thereby effectively maintaining a large nanostructure surface area exposed to the electrolyte.…”
Section: Synthetic Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Fig. 2f and g display the SEM images of the precursor WO 3 and the resulting α-SnWO 4 nanorod arrays obtained by Qiu et al , 56 respectively. These images reveal that the conversion process did not significantly alter the morphology of the nanorods, thereby effectively maintaining a large nanostructure surface area exposed to the electrolyte.…”
Section: Synthetic Methodsmentioning
confidence: 98%
“…This method was further improved by several researchers, including He et al [55][56][57] They synthesized nanostructured α-SnWO 4 thin films on fluorine-doped tin oxide (FTO) substrates using approximately the same method as described by Pyper et al, but with the addition of a post-annealing process conducted at 500 °C under an Ar atmosphere. 57 It was argued that the annealing step under an inert atmosphere would influence the oxidation state of α-SnWO 4 , preventing the formation of Sn 4+ .…”
Section: Conversion From Womentioning
confidence: 99%
See 1 more Smart Citation
“…The material shows n-type conductivity, which means that it should be employed as the photoanode in PEC water splitting devices. Several studies have been reported in the last few years on α-SnWO 4 films prepared by different techniques, [10][11][12][13][14][15][16][17][18][19][20][21][22] e.g., hydrothermal synthesis, reactive magnetron sputtering, pulsed laser deposition, and chemical vapor deposition. The attractive properties of this material as a photoanode include the bandgap of 1.9 eV, which is close to ideal for use as a top absorber in a tandem configuration, and the favorably low onset potential of %0 V versus RHE.…”
Section: Introductionmentioning
confidence: 99%
“…[18,25] Epitaxial or highly oriented films are therefore expected to have much improved charge transport, and indeed recent reports on two-dimensional α-SnWO 4 crystalline nanosheets with preferred {001} orientation demonstrated superior performance. [18][19][20] Another limitation is the modest photovoltage that can be extracted from the material, despite the fact that the band positions straddle the water reduction and oxidation potentials (which would enable a maximum quasi-Fermi level splitting of at least 1.23 V under operating conditions). In our earlier study on NiO x -coated α-SnWO 4 , in which the NiO x serves as the protection layer, we showed that the limitation of the photovoltage can be correlated with the formation of an interfacial oxide layer at the interface of α-SnWO 4 and NiO x .…”
Section: Introductionmentioning
confidence: 99%